ANALYSIS OF SELF-CONTROL IN THE FORMATION OF AN ASSOCIATION OF OVERSEAS STUDENTS ON THE LEADERSHIP PATH SEI KERA HILIR I - Irma Widia; Winda Kustiawan (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Merantau is an activity carried out by someone who leaves his hometown on his own accord within a predetermined period of time with the aim of seeking life, studying knowledge and seeking experience. At this time, adolescents should begin to learn to have responsibilities who are able to think and act according to the norms prevailing in society. Self-control is an ability possessed by individuals, in this case students, to control or control themselves, both in terms of their behavior, thoughts and choices of decisions to be taken by these individuals. Overseas students need self-control so that the trust that their parents give them is maintained properly. This study aims to analyze self-control in the formation of overseas student associations in Sei Kera Hilir I village, Medan. The method used in this research is descriptive qualitative. The sample used in this study were overseas students who were in Deda Sei Kera Hilir I, obtained by snowball sampling technique. The results of interviews with informants show that students feel a new life in the overseas environment and the self-control of every student who migrates is certainly different. There are those who apply it by contemplating in the room alone, there are those who invite other friends to exchange stories and some of them definitely hide things that are not good about not wanting to bother their friends. The causal factors are family conditions in the village, coursework, economics and others. It is conducted that forms of self-control in overseas students are behavioral control, cognitive control, and satisfaction control.